1985
DOI: 10.1093/infdis/152.6.1159
|View full text |Cite
|
Sign up to set email alerts
|

Rehydration and Maintenance Therapy of Cholera Patients in Jakarta: Citrate-Based Versus Bicarbonate-Based Oral Rehydration Salt Solution

Abstract: We compared the therapeutic efficacy of a World Health Organization standard bicarbonate-based oral rehydration salt solution (BBORS) with a citrate-based oral rehydration solution (CBORS) in a randomized, double-blind, controlled trial in 130 dehydrated patients with cholera aged three to 82 years. On admission the 70 patients who received CBORS and the 60 who received BBORS were similar except that the serum CO2 content (mmol/liter) was significantly lower in the CBORS group (10.8 +/- 3.6 vs. 12.5 +/- 5.3). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…In view of the serious packaging problem with oral rehydration salts containing bicarbonate, base precursors like acetate (10) and citrate (11,12) have been used in place of bicarbonate. Whether such base substitutes are also capable of enhancing sodium absorption from the small intestine in the same way as bicarbonate, has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the serious packaging problem with oral rehydration salts containing bicarbonate, base precursors like acetate (10) and citrate (11,12) have been used in place of bicarbonate. Whether such base substitutes are also capable of enhancing sodium absorption from the small intestine in the same way as bicarbonate, has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…A solution containing glucose polymer also proved to be as effective as other ORS containing glucose monomers in a controlled clinical trial recently completed at the Queen Elizabeth Hospital for Children in London (44). Further indication of their efficacy derives from the results of clinical trials using ORS where glucose was substituted by rice-powder which contains [80][81][82][83][84][85][86][87][88] % carbohydrate in the form of polymers. Several controlled clinical trials (20,30,(46)(47)(48) have shown that rice-ORS is at least as effective as WHO-ORS in the treatment of dehydration from acute diarrhoea of various aetiologies.…”
Section: Curhohydratementioning
confidence: 99%
“…Bicarbonate was originally included in WHO-ORS but practical and economic problems have prompted the search for other alternatives. Controlled clinical trials have shown that acetate (84) and citrate (25,81,(85)(86)(87) containing ORS are at least as effective as WHO-ORS with bicarbonate for correcting dehydration and acidosis. Bicarbonate has recently been replaced by citrate in WHO-ORS to obtain greater stability of solutions.…”
Section: Base or Base Percursorsmentioning
confidence: 99%
“…In clinical trials, omission of bicarbonate [2][3][4], or its replacement with acetate [5,6], citrate [7][8][9] or lactate [10] in oral rehydration solutions has had little or no measurable effect on recovery rates from gastroenteritis, although the correction of any acidaemia may be delayed. The presence of bicarbonate or base precursor in oral rehy dration solutions has been proposed par tially on the basis that they enhance sodium and water absorption and they may poten tiate the effect of glucose.…”
Section: Introductionmentioning
confidence: 99%